THE CALCULATION METHOD OF IN-DEBT LAND AND PROPERTY TAX BASED ON THE PERSONAL PAYMENT ABILITY - (NIM 25106021), MAHFUD
A fair tax system at least have to fulfill three criterions. First, tax must be collected to finance proper thing and to realized social welfare; second, tax should not overburden compared to taxpayer's ability, and must be distributed fairly among every taxpayer; and third, the result must be spend prudently in line with tax collection objective. The purpose of this research is to find a counting method of in debt PBB which can fulfill second criterion from three mentioned criterion above. The current counting method may generate tax overburden so the taxpayer might not be able to pay their PBB obligation. In making the method, first researcher collects spatial data and non-spatial data from KPP Pratama Bandung Cibeunying, correlates both data based on neighborhood, and proposes several in-debt PBB counting methods based on the available data. From the result of data processing, it can be concluded that the usage of properties and income measure can minimize appearance PBB burden which exceed the taxpayer's ability, and if required, there is a mechanism to redistribute PBB burden as a result of reduction, which can be done proportionally based on taxpayer's income.